Psychological interventions for cancer-related post-traumatic stress disorder: narrative review - Daniel Anderson; Victoria Jones (BJPsych Bulletin)
Aims and method This narrative review updates the evidence base for cancer-related post-traumatic stress disorder (PTSD). Databases were searched in December 2021, and included EMBASE, Medline, PsycINFO and PubMed. Adults diagnosed with cancer who had symptoms of PTSD were included.